Novel Corona Virus: Its Origin, Current Dignosis And Various Diseases Arises Due To Covid-19 - B, Gawali Mangesh; R, Sangle Rahul (Asian Journal of Pharmaceutical Research and Development, 2021)
Severe Acute Respiratory Syndrome Coronavirus-2 is responsible for the emergence and propagation of new coronavirus illness 2019 i.e. COVID-19, have posed a significant threat to global public health. Coronaviruses are enveloped single positive-stranded RNA viruses with the biggest viral genome (26-33kb) among the RNA viruses, belonging to the Corona viridae family.This potentially deadly virus spreads quickly from person to person. To control the epidemics of COVID-19, large-scale measures such as isolation of infected patients, social distancing, frequent washing of hands, and the usage of face masks have been implemented.In this review, we provide a brief overview of the highly pathogenic Severe Acute Respiratory Syndrome Coronavirus outbreaks,its origin, symptoms, clinical features, preventive measures, current diagnostic tools and therapeutic strategies. We also discuss about various diseases arises due to COVID-19 pandemic.